Does a Consumer’s Religion Really Matter in the Buyer–Seller Dyad? An Empirical Study Examining the Relationship Between Consumer Religious Commitment, Christian Conservatism and the Ethical Judgment of a Seller’s Controversial Business Decision - Swimberghe, Krist R.; Sharma, Dheeraj; Flurry, Laura Willis (2011)
Religion is an important cultural and individual difference variable. Yet, despite its obvious importance in consumers’ lives, religion in the United States has been under-researched. This study addresses that gap in the literature and investigates the influence of consumer religion in the buyer–seller dyad. Specifically, this study examines the influence of consumer religious commitment and a Christian consumer’s conservative beliefs in the United States on store loyalty when retailers make business decisions which are potentially reli- gious objectionable. This study uses structural equation modeling and applies Anderson and Gerbing’s (Psychol Bull 103(3):411–423, 1988) two-step approach to exam- ine data obtained from a national sample of 531 consumers. The results from this study suggest that consumers evaluate seller’s actions and form ethical judgments. These judgments are a major explanatory variable in consumer store loyalty intentions.
Keywords: Social Responsibility; Christian conservatism; Religious Commitment; Ethical Judgment